Experiências relacionadas à ideação suicida em mães adolescentes: estudo clínico-qualitativo - LAGES, Laíse de Souza (2021)
Introduction: It started from the need to understand the existing relationships between suicidal ideation in puerperal women and the influence of the environment in which it is inserted, based on the Theory of Interpersonal Relationships of approach. Objective: To know the experience and feelings of suicidal ideation of teenage mothers during pregnancy and the puerperium. Methodology: Clinical-qualitative research, carried out in two maternity hospitals in the Northeast of Brazil as a natural setting for the research. Developed in Accomodation with 11 teenagers between 17 and 19 years old, through the recording of the reports Then there was the complete transcription of the reports. After the floating reading of the corpus of the study, the data collected in the interviews were treated, advancing to the categorization in topics and leading to the discussion of the results, correlating the meaning of the reports with the theoretical foundation. The technique of clinical-qualitative analysis of the content comprised seven steps: 1) Editing of material for analysis; 2) Floating reading; 3) Construction of the analysis units; 4) Construction of meaning codes; 5) General refining of codes and construction of categories; 6) Discussion and; 7) Validity. The external validation of the results occurred at a later time with people with expertise in the theoretical and methodological framework. Results: The adolescents interviewed were aged between 17 and 19 years old and were accompanied during hospitalization. Of the 11, eight live in a stable relationship and three are single, living in the home of their parents or guardians. As for education, four finished high school, four dropped out of school due to lack of interest and three remained with their studies temporarily paralyzed due to the Covid-19 pandemic. In terms of income, two adolescents work informally and nine do not. Three categories emerged: 1) Causes of suicidal ideation; 2) From suicidal ideation to suicide attempts, which depicts the ways used to carry out the suicide attempt; 3) Life after suicide attempts. Final Considerations: By understanding the situations experienced by adolescent mothers, the following categories were identified: the adolescents' opinion on the reasons for suicidal ideation, addressing unstable, distant and absent parental relationships and marital relationships based on physical and psychological violence and marked for infidelity and abandonment; the experiences of suicidal ideation and suicide attempts during life through exogenous intoxication, self-mutilation behavior and hanging attempts; and following episodes of suicidal ideation through feelings of overcoming by maternal and religious support and maternal feeling and not overcoming.